Tunable degree of oxidation through variation of H2O2 concentration and its effect on structural, optical and supercapacitive properties of graphene oxide powders synthesized using improved method. (December 2017) - Kumar, Sumeet; Baruah, Bhagyalakhi; Kumar, Ashok
Graphical abstract: Abstract: Graphene oxide (GO) powders have been synthesized via improved method (also called Tour's method) by varying concentration of H2 O2 and the effect of H2 O2 concentration on its properties has been studied extensively. The synthesized samples were characterized by XRD, TEM, Raman, FTIR and UV–Vis. spectroscopy. The degree of oxidation level in the synthesized samples was estimated from obtained results and the fundamental aspects of correlation between their properties and the degree of oxidation is discussed exclusively. Our results demonstrate that the use of different concentrations of H2 O2 can control the surface and molecular structures of GO, resulting in the tunable structural, optical and electrochemical properties which could be useful for supercapacitor applications.